Characterization of structural conditions for pavement rehabilitations. (15th September 2016) - Chen, Dar Hao; Scullion, Tom; Nam, Boo Hyun
Highlights: TPAD has been used successfully to identify problematic areas with very poor load transfer. GPR is integrated into TPAD and able to detect trapping moisture in the subsurface layers. The responsible district has implemented TPAD results for pre-overlay treatment. Abstract: For concrete pavements it is critical to identify weak spots and locations with very poor load transfer efficiency and then to apply localized repairs before placing a structural overlay. Collecting a continuous deflection profile is the most efficient way to identify those locations. The Texas Department of Transportation's Total Pavement Acceptance Device (TPAD) has been used successfully on two field projects with main goal of identifying these problematic areas. TPAD is an integrated nondestructive testing tool and it collects continuous deflections at approximately 50 mm intervals with three rolling geophone sensors while traveling over the pavement at 2 mph. Empirical threshold values have been established to identify and prioritize the problematic areas. Refinements to the threshold values can be made with additional field performance monitoring data. In addition to continuous deflections, the TPAD unit also collects continuous Ground Penetrating Radar (GPR) data. In a project on IH 20, the GPR data presented clear evidence that there are wet areas beneath the existing concrete slabs due to clogged edge drains. Trapped moisture is one of the main causes for the recurring failures observed on IH20. On the jointed concrete pavement on Loop 12 in Dallas, five different short sections with high deflections were successfully identified. The responsible district has implemented recommendation for pre-overlay treatment on those five short sections through full depth repairs. The TPAD data provides quantifiable and defensible data for selecting the required repair areas before the overlay to minimize premature failures. With its continuing utilization and additional field performance monitoring, it is anticipated that the refinements to the threshold values for TPAD analyses can be made.